Pelatihan Kaligrafi Jepang sebagai Produk Seni dan Sarana Pengembangan Keterampilan Menulis Kana bagi Siswa SMK Kartika 1-2 Padang - Putri, Meira Anggia; Faisal, Dini; Oktoviandry, Rifki; Wikarya, Rahmi Oktayory (Universitas Negeri Padang, 2025)
The purpose of this community service activity was improving students understanding and mastery in Japanese calligraphy (shodō) as the medium to develop kana writing skill. The programme was implemented at SMK Kartika 1-2 Padang involving the 23 students. The training was developed with an educational and innovative focus, structuring it with lectures, discussion, demonstration, and guided practice. Two kinds of features were focused: (1) The knowledge on Japanese calligraphy and the ways of writing kana and (2) Practical skills for making Japanese calligraphy works. The results of the pretest showed that most students’ knowledge of Japanese calligraphy was still at a low level, with an average score of 56.1. After the training, the posttest results demonstrated significant improvement, with the average score rising to 85.5. More than half of the students (52.17%) reached the “very good” category. From the practical perspective, each student successfully produced one piece of Japanese calligraphy artwork, showing progress in accuracy, neatness, and creativity. In conclusion, the integration of Japanese calligraphy into learning activities proved effective in improving both knowledge and practical skills. This method not only supports students’ language learning outcomes but also fosters cultural appreciation, creativity, and active engagement in the learning process.